CONCEPTUAL PRINCIPLES OF EDUCATION THE SPECIALISTS FOR THE SOCIAL PROTECTION SYSTEM IN THE BANKING UNIVERSITY - Смовженко, Тамара; Скринник, Зоя (Socio-economic relations in the digital society, 2019)
The article contains an explication of the conceptual principles of the education in a new specialty 232 "Social Protection" in Banking University. Th eir importance for the development of the University is outlined: it is strengthening of the humanitarian component of the educational process and, on the other hand, the possibility of application of competencies in the fi eld of fi nancial-banking, insurance, entrepreneurship to solving urgent tasks of social protection in Ukraine. The features of the new specialty are exposed, which to a large extent go beyond the model of a specialist, traditional for the Banking University. It was demonstrated that the education of specialists for the social protection system encourages a substantial expansion of the topics of the research work in the University, separately, in the Lviv Institute. A number of actual problems of the modernization of social policy in Ukraine are outlined that require deep scientifi c research and are suitable for the content of the scientifi c interests and the theoretical potential of the University. Thus, it is necessary to develop a system for improving the qualifications of teachers who will be involved in the educational process in this specialty, in the bodies and institutions of the social security system. it should be borne in mind that the specifics of the new specialty largely go beyond the model of a specialist, traditional for the "UBS". It is expedient to involve practitioners in the educational process from the fi rst year of study; inclusion of students in the work of public organizations and social movements. Substantial expansion should acquire the topics of research work of the faculty, taking into account the peculiarities of the issues of social protection and provision. these features, in contrast to the scientifi c research, traditional for UBS, are marked by a considerably lower level of development of recommendations for a new paradigm of the above-mentioned branches of social policy in Ukraine.
Keywords: social security; social protection; coaching of specialists; social policy; educational program